An Analysis of English Teachers’ Speaking Skill at the Coastal Schools in Bengkulu City - Ildi Kurniawan (AL LUGHAH, 2019)
This study aims to illustrate the speaking skills of English teachers on the coastal school of Bengkulu City as well as the factors that influence the speaking skills. This research was a descriptive-qualitative research which was also a continuation of previous research on students' speaking skills in the coastal area. The subjects of this study were English teachers who attended school, namely English teachers at SMAN 6 Kota Bengkulu, SMAN I Kota Bengkulu and SMAN 7 Plus Kota Bengkulu, SMPN 7 Kota Bengkulu, SMPN 1 Kota Bengkulu, SMPIT Iqra 'Kota Bengkulu, SMPN 15 Kota Bengkulu. Data that has been obtained in the form of audio-visual recordings when the teacher spoke English, as well as an interview recording related to the speaking skills of the English teacher. The data obtained were analyzed, interpreted and concluded as findings by using the Interactive Model technique namely reduction, display, drawing a conclusion. The results of this study indicated that the English teachers’ speaking skills at the Bengkulu City coastal school was at a moderate level. Fluency in speaking was the main problem faced by these teachers. In addition, grammar also became an obstacle for them. While the identified factors that couldinfluence the English teacher's speaking skills were the internal factors of English teachers themselves who often used Indonesian language when teaching rather than English itself with the reason that children would easily understand the message or subject matter when compared to English. In addition, curriculum change as an external factor was also a reason for English teachers not to speak English much in class with the latest curriculum consideration, namely the 2013 Curriculum requires active students, not teachers